Countering piracy through private security in the Horn of Africa: prospects and pitfalls. Issue 5 (3rd May 2016) - Affi, Ladan; Elmi, Afyare A.; Knight, W. Andy; Mohamed, Said
Abstract: Employing secondary research and semi-structured interviews, this article examines the use of private maritime security companies (PMSC) in providing maritime security services in the Horn of Africa. It consists of four parts. The first part explains the origins and development of the use of PMSC in the Horn of Africa. The second section discusses the regulation of the private security industry, paying particular attention to the maritime context. Part three examines the challenges associated with the use of maritime PMSC in the Horn of Africa, including negative human rights implications, compromising the innocent passage of commercial ships, and creating confusion in the hierarchical control of ships. Finally, the paper analyses the findings and concludes that PMSC, despite their apparent short-term effectiveness, cannot be regarded as a long-term solution to the piracy phenomenon in the Horn of Africa.